Avaliação do desvio lateral do feixe em protonterapia - Cassetta Junior, Francisco Roberto (2013)
This work developed a study of the lateral deviation of the beam used in proton therapy. Through software, such as SRIM2012 and GEANT4, which allow simulations of heavy particles passing through matter, it was possible to obtain results for specific studies in this area. The importance of these simulations comes from its simplicity of use mainly due to the high cost of hadron accelerators and the huge variety of possibilities for methods analysis. The proton therapy has shown promising results compared to conventional treatment by photons, the analysis of the parameters calculated by simulations and their levels of uncertainty in the region of the Bragg peak will be essential for future improvements of treatment plans in proton therapy. Targets used were composed of water and also of human tissue substitute materials for scattering analysis of the proton beam, and the results show the trend of increased lateral deviation with initial energy of the beam increasing in the region of maximum range of protons, where we find the Bragg peak, and this lateral uncertainty has the same order of magnitude than the uncertainty in depth found in the current literature.